Implementation of social emotional learning skills - Ismail Ismail; Muhammad Abrar Parinduri (Jurnal Sinar Edukasi, 2025)
The fact that the era we are living in is a global one with all its changes makes it impossible to separate it from the world of education. With the changes in this era, students are not only focusing on learning core competencies in their subjects, but also on mastering various skills needed in the 21st century. Educators must be able to adapt to the diverse changes that exist and must be able to equip and enhance their knowledge of various global issues. The concept of social-emotional learning is one of the educational issues currently being promoted. The research method used in this study is descriptive qualitative. This research aims to describe the implementation of social-emotional learning skills applied at Madrasah Aliyah X in Medan City. Based on the findings of the research above, it can be concluded that students attending Madrasah Aliyah X in Medan City have partially implemented SEL (Social Emotional Learning). This is due to the support of educators and school programs that promote skills in the field of SEL.